Effect of Temperature and Composition on the FTIR Spectroscopic Properties of Barium Ferrite Compounds: Analysis of Intensity and Peak Position - Méité, Namory; Sarkingobir, Yusuf; Kouamé, Alfred Niamien; Sanou, Ali (Lensa: Jurnal Kependidikan Fisika, 2026)
This study analyzes the effect of temperature and composition on the FTIR spectroscopic properties of Barium Ferrite (BaFe) compounds, which have important applications in magnetic technology and data storage. The BaFe samples were synthesized with variations in cobalt (Co) and zinc (Zn) composition at different temperatures to examine changes in peak positions and intensities in the FTIR spectrum. The results show that the processing temperature affects the crystalline structure of BaFe, where increasing temperature leads to a decrease in the intensity of several major peaks, reflecting changes in metal-oxygen bonds and degradation of crystalline bonds. Meanwhile, variations in composition with the addition of Co and Zn increase the peak intensity in the FTIR spectrum, strengthening bond vibrations and improving material stability. This study provides important insights into how temperature and composition can influence FTIR properties in BaFe, which is relevant for applications such as permanent magnet production and magnetic data storage materials. These findings are expected to assist in the development of BaFe materials with more optimal magnetic and optical properties for various technological applications.